2021
DOI: 10.3390/nu13124522
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Eating Habits and Physical Activity after COVID-19 Pandemic Lockdowns in Italy

Abstract: The introduction of lockdowns and other containment measures during the COVID-19 pandemic substantially altered people’s lifestyle and dietary behavior. Several studies evaluated the short-term effects of these measures; yet reports on long-term consequences are scarce. We sought to address this gap in the literature by analyzing dietary and lifestyle data collected at an obesity center in Rome, Italy. The Italian region of Lazio was hit hard by the pandemic. To evaluate the potential health impacts, we compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…In addition, while 40.8% of Q1 respondents indicated reduced physical activity as a probable reason for weight change, 17.6% of Q1 respondents indicated they had greater frequency, intensity, and/or duration of exercise, which had a beneficial impact on weight control. Although recent studies have reported significant pandemic-related changes in weight and increased snacking among large segments of the population, this study's participants did not exhibit those behaviors to similar extremes [27,[31][32][33]. Qualitative data also support this, as 17.6% of Q1 respondents indicated improved eating habits.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, while 40.8% of Q1 respondents indicated reduced physical activity as a probable reason for weight change, 17.6% of Q1 respondents indicated they had greater frequency, intensity, and/or duration of exercise, which had a beneficial impact on weight control. Although recent studies have reported significant pandemic-related changes in weight and increased snacking among large segments of the population, this study's participants did not exhibit those behaviors to similar extremes [27,[31][32][33]. Qualitative data also support this, as 17.6% of Q1 respondents indicated improved eating habits.…”
Section: Discussionsupporting
confidence: 52%
“…The COVID-19 pandemic situation has been a turning point in daily life, resulting in major changes in daily, social, and work habits [ 1 , 2 , 3 ]. Among these transformations, the imposition of the mandatory use of facemasks in many countries as a sanitary measure stands out [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients 2022, 14, 2572 2 of 18 The outbreak of the global pandemic COVID-19 has produced a sudden disruption in people's routines with waves of uncertainties and pronounced anxiety. Factors such as sickness, loss of lives and jobs, shift to remote working, and adaptation to a new norm came with a hefty toll on mental health [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…During lockdowns, physical exercise routines were interrupted for many [18]. Stereotypically, people are accustomed to going to the gym to work out; however, unwillingly many elected to exercise at home.…”
Section: Introductionmentioning
confidence: 99%